Anxiolytic-like effect of Citrus limon (L.) Burm f. essential oil inhalation on mice - M.D.M. VIANA; R.M. CARDOSO; N.K.G.T. SILVA; M.A.P. FALCÃO; A.C.S. VIEIRA; M.S. ALEXANDRE-MOREIRA; E.A. CAMPESATTO (Universidade Estadual Paulista, 2016)
ABSTRACT Experimental in vivo study aimed to characterize the anxiolytic-like effect of the Citrus limon fruit peel's essential oil (CLEO) in animal models of anxiety, besides evaluating the viability J774.A1 cells in vitro through the MTT reduction method at the concentrations of 10 and 100 µg/mL. The anxiolytic behavior was evaluated in Swiss mice (n = 8) using the methodology of Elevated Plus-Maze (EPM) and Open-Field (OF). CLEO was tested by inhalation at the doses of 100, 200, and 400 µL, and as control, animals were subjected to inhalation of the vehicle (saline solution 0.9% + Tween80®) and intraperitoneal administration of diazepam (1.5 mg/kg). In the cell viability assay, it was observed that none of the concentrations showed cytotoxicity. OF test showed significant anxiolytic activity at all tested doses of OECL, compared to the control group, without changing the motor performance of the animals. Corroborating OF data, the EPM test confirmed anxiolytic activity in at least two doses of the tested oil (200 and 400 µL), justified by the number of entries and increase in the percentage of time in the open arms. The data analysis of this study evidenced that inhalation of OECL was able to induce an anxiolytic behavior in mice; however, further studies are required to ensure its safe use by the population.